Denaturation of egg white: a simple Biochemistry experiment for teaching Biology (Research, Society and Development, 2021)
Proteins are one of the most important and incredible molecules in life. However, when exposed to adverse conditions such as temperature variation, pH and even organic solvents, they undergo denaturation, changing their shape and losing their function. This article has as main objective to propose a practical class to facilitate the learning of the protein denaturation theme to high school students, in the discipline of Biology. For this, simple and low-cost material resources will be used, such as the white of a hen's egg, disposable cups or transparent test tubes, vinegar (acetic acid) and 70% alcohol. By submitting albumin (protein present in egg whites) in different treatments, students will check whether it will denature or not, discussing and rescuing the theoretical concepts previously learned in the discipline of Biology. In this way, we believe that the practice of scientific experimentation combined with discussions mediated by the teacher can enhance the students learning in the proposed topic, thus demystifying that Biochemistry is a complex area.